2023
DOI: 10.3847/1538-3881/acafee
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Clouds in a Section of the Third Galactic Quadrant: Cloud Catalog

Abstract: We present results of cloud catalogs of 12CO, 13CO, and C18O (J = 1–0) in a section of the third Galactic quadrant over (195° < l < 220°, ∣b∣ < 5°) from the Milky Way Imaging Scroll Painting project. The data were acquired with the PMO 13.7 m millimeter telescope with ∼50″angular resolution. We construct three molecular cloud catalogs containing information of 12CO, 13CO, and C18O from the position–position–velocity (PPV) data cubes. The 12CO cloud catalog contains 7069 samples identified based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The data cover a section in the third Galactic quadrant (195°< l < 220°, |b| < 5°) and are part of the Milky Way Imaging Scroll Painting (MWISP) project, which is a multiline Galactic plane survey in CO and its isotopic transitions. The mean noise σ is ∼0.45 K for 12 CO with 0.16 km s −1 velocity resolution and ∼0.25 K for 13 CO and C 18 O with 0.17 km s −1 velocity resolution (Wang et al 2023).…”
Section: Data and Catalogmentioning
confidence: 93%
See 1 more Smart Citation
“…The data cover a section in the third Galactic quadrant (195°< l < 220°, |b| < 5°) and are part of the Milky Way Imaging Scroll Painting (MWISP) project, which is a multiline Galactic plane survey in CO and its isotopic transitions. The mean noise σ is ∼0.45 K for 12 CO with 0.16 km s −1 velocity resolution and ∼0.25 K for 13 CO and C 18 O with 0.17 km s −1 velocity resolution (Wang et al 2023).…”
Section: Data and Catalogmentioning
confidence: 93%
“…This paper is the third in a series of studies on large samples of MCs in this region. In Paper I (Wang et al 2023), the data were described in detail, and 7069 clouds were identified based on the DBSCAN algorithm in the 12 CO data. Additionally, we identified 1197 clouds with 13 CO emission and 32 clouds with C 18 O emission based on the stacking bump algorithm in the catalog of 7069 clouds.…”
Section: Co C O 13 18mentioning
confidence: 99%
“…Oliver et al (1996) performed a detailed CO study toward the Mon OB1 region based on the CfA 1.2 m telescope. The distribution of column density and the abundance ratio of molecular gas (C 18 O/ 13 CO) in the region were also investigated recently (Ma et al 2022;Wang et al 2023a).…”
Section: Introductionmentioning
confidence: 99%
“…We also try to estimate the mass of dense gas traced by C 18 O. Here we use the stacking bump algorithm (Wang et al 2023a) to search for the C 18 O signal within the 13 CO boundary. Briefly, the identified C 18 O signal satisfies the following conditions: (1) For each identified pixel, at least three continuous channels of the spectrum are larger than two times the rms noise (∼0.5 K).…”
mentioning
confidence: 99%
See 1 more Smart Citation